PERAN SOSIO-KULTURAL PEREMPUAN DALAM KELUARGA NELAYAN DI DESA KEDONGANAN, BALI - Suryawan, Irfa' Ade; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT Role of socio in the domestic sector si seen form the interaction in the family while the public sector is seen from the interaction with the community. The cultural role is associated with Panca Dharma Wanita. There are roles that can be performed in the public sector and there can be done in the public sector. The role was performed in accordance with the status of the family as a mother or wife and also as a daughter. The impact of domestic roles is home hygiene, child education, interaction with family, additional living and other necessities that can be fulfilled. While the public role of the impact is an assisted economy, it can interact with the community as well as increased experience and knowledge. The research was in the analysis using Social Construction Theory by L. Peter Berger and Thomas Luckmann. Keywords : Female roles, Socio-Cultural, Imapct